Temporal variability of the Io plasma torus inferred from ground-based [SII] emission observations - Fabíola Pinho Magalhães (2016)
Jupiter${'}$s magnetosphere is the largest one in the Solar System. It is a very complex system with several moons embedded, effects of planetary corotation and solar wind driven convection superposed, and several plasma physics processes occurring. Immersed within the magnetospheric plasma are the four Galilean moons which orbit around Jupiter. Io, the innermost of Jupiter${'}$s four Galilean moons, is the principal source of the magnetospheric plasma and responsible for nearly 1 ton/s of ions introduced into Jupiters magnetosphere. Io has intense and energetic volcanic activity. The sulfur and oxygen present in Io${'}$s tenuous atmosphere, spewed by volcanoes, escapes forming an extended neutral cloud around Io and Jupiter. Subsequently, by ionization and pickup ions, a ring of charged particles encircling Jupiter is created, forming the Io plasma torus. The Io plasma torus is composed mainly of sulfur and oxygen ions. Also via atmospheric escape, an extended neutral is formed, composed mainly of sodium. The torus is about 2 Jupiter radii (R$_{J}$ = 71,492 km) in width and is centered on Ios orbit around Jupiter at a distance of $\sim$ 5.9 R$_{J}$ . Considering this scenario, it is reasonable to expect that the Io plasma torus should be affected by changes in Io${'}$s volcanism. With that thought in mind, this thesis presents the analysis and results of the ground-based observations of the [SII] 6731 Å emission lines from the Io plasma torus for the year 1997. The observations occurred at the McMath-Pierce Solar Telescope at Kitt Peak and the data is part of a collaboration established during this thesis. The plasma torus is most dense around Io${'}$s orbit and from the [SII] 6731 Å emission lines we were able to obtain the brightness of both ansae. By conducting the Lomb-Scargle peridiogram we tried to measure the system III and IV periodicities. Due to a problem with scattered light too close to the ansae position, the results showed an amount of noise that does not allow a precise location of system IV. The importance to identify the system IV is the hypothesis that it is related to material radial transport through the Io plasma torus. Interactions between Io and the Jovian environment, particularly the Io plasma torus, are unique and not well understood. With this thesis we aim to improve the understanding of this complex coupled system.